Legacy of the puppy : the ultimate illustrated guide - Ueki, Hiroyuki (Chronicle Books, 2004)
Presents an illustrated guide to dogs, arranged by breeding group, and contains information on the temperament, trainability, energy level, height and weight, personality traits and exercise requirement for each breed.